INTEGRASI TEKNOLOGI PENDIDIKAN DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM: Integration Of Educational Technology In The Islamic Religious Education Curriculum - Khoirul Anas Abror; Ary Asyari (STAI Ma'had Aly Al-Hikam Malang, 2026)
article aims to examine the integration of educational technology into the Islamic Religious Education (IRE) curriculum through a qualitative literature review. Data were obtained from various sources, such as academic articles and books, which were retrieved online. Content analysis was used to identify the concept of educational technology integration within the PAI curriculum. The findings indicate that technology serves not only as an innovation in learning but also as a means to reinforce Islamic spiritual values in the digital age. Through the Humanistic–Religious Constructivism paradigm, PAI functions not merely as an instrument for transferring dogma or knowledge but as a catalyst for digital spiritual transformation through dialogic, reflective, and contextual learning. To support digital integration in the PAI curriculum, teachers need to be equipped with technological, pedagogical, and spiritual-reflective skills. Artikel ini bertujuan mengkaji integrasi teknologi pendidikan ke dalam kurikulum Pendidikan Agama Islam (PAI) melalui pendekatan kualitatif dan jenis studi literatur. Data diperoleh dari berbagai sumber seperti artikel ilmiah dan buku yang ditelusuri secara daring. Teknik analisis isi digunakan mengidentifikasi konsep integrasi teknologi pendidikan dalam kurikulum PAI. Hasil kajian menunjukkan bahwa teknologi tidak hanya berfungsi sebagai inovasi pembelajaran, tetapi juga sebagai sarana untuk memperkuat nilai-nilai spiritual Islam di era digital. Dengan paradigma Humanistic–Religious Constructivism, PAI tidak hanya berfungsi sebagai instrumen transfer dogma atau ilmu, melainkan transformasi spiritual digital melalui pembelajaran yang dialogis, reflektif, dan kontekstual. Untuk mendukung integrasi digital dalam kurikulum PAI, maka para guru perlu dibekali keterampilan teknologi, pedagogik dan spiritual-reflektif. Kata Kunci : Integrasi Teknologi; Kurikulum PAI; Pendidikan Agama Islam; Teknologi Pendidikan.